Upaya Guru Dalam Menggunakan Model Pembelajaran Flipped Classroom Untuk Meningkatkan Pemahaman Materi Sejarah Siswa - Besari Arkan; Dita Hendriani (Jurnal Ilmu Pendidikan dan Sosial, 2023)
The teacher's efforts are actions carried out by a teacher in order to achieve a predetermined goal. While understanding a material is the ability to express and interpret, to make difficult words in their own words, to interpret ideas or find an event or result. Learning model flipped classroom is a standard model or method that minimizes direct instruction from the teacher. In the program, students learn basic concepts at home, teach and learn in class, including homework, discussion of material, or problem solving during class. The aims of this study are 1) to define the teacher's efforts in using the model flipped classroom, 2) define the obstacles experienced by the teacher in using the model flipped classroom and 3) define student responses as recipients of historical material using models flipped classroom. The method used in this research is qualitative with a case study type of research. Through this research the results were obtained in the form of: 1) the efforts made by the teacher in using the model flipped classroom one of which is to prepare power point material that will be given to students clearly, 2) the obstacles experienced by the teacher in trying to use the model flipped classroom one of which is the long time for making learning media in the form of power point, 3) student responses as recipients of historical material using models flipped classroom one of which is that students are very active and often give responses and questions to friends and teachers who are presenting in class